ЎЗБЕК ХАЛҚИ ЭТНОГЕНЕЗИ ВА ЭТНИК ТАРИХИ МУАММОСИНИНГ АНТРОПОЛОГИК ТАДҚИҚОТЛАРДА АКС ЭТИШИ (Scientific journal of the Fergana State University, 2023)
The article examines the issue of ethnogenesis and ethnic history of the Uzbek people as a result of anthropological research in the region